Roles of Dispersal Limit and Environmental Filtering in Shaping the Spatiotemporal Patterns of Invasive Alien Plant Diversity in China - Li, Yiying; Shen, Zehao (Frontiers in Ecology and Evolution, 2020)
Biological invasion pose a severe threat to global biodiversity, and studies of bioinvasion patterns and the underlying mechanisms provide critical tests to ecological theories. China is a global hotspot of biodiversity and also biological invasions. The understanding of mechanisms for bioinvasion patterns has been limited by inadequacy of data spatial resolution, and lack of a historical perspective. This study compiled the first nation-scale distribution data with a sub-provincial spatial unit (prefecture) for 463 invasive alien plants species (IAPS) recorded in China, as well as their introduction times. The spatiotemporal patterns of species richness of invasive alien plants, including three life forms (annual-biennial, perennial, and woody) were explored, then related the species richness patterns with environmental, social-economic and historical factors. Statistical analyses included quantile regression, generalized linear model (GLM), and hierarchical variation partitioning. The results indicated that: 1) herbaceous species comprised 84% of the 463 IAPS in China; 2) plant introductions into China accelerated since 1800, reaching the maximum rate during 1900-1940. IAPS richness had a closer correlation with the time of newest introduction (R2=0.155) than with that of the oldest introduction (R2=0.472); 3) IAPS richness decreases with increasing latitude (r = –0.32, P<0.001) and decreases from the coastal and southern terrestrial borders to inland regions, but doesn’t increase with prefecture size. The three life forms of IAPS showed similar latitudinal patterns of species richness and divergent latitudinal patterns of species percentage. 4) IAPS richness showed significantly positive correlations with thermal climate and a negative relationship with climate seasonality. GLM explained up to 65% of the variation in spatial patterns of IAPS and three life forms; with much less variation explained in the species percentage patterns. The year of the most recent IAPS introduction and the low temperature limit jointly dominated spatial patterns of IAPS richness in China, whereas road density showed little effect. Therefore, global warming and economic globalization play a prominent role in promoting biological invasion in the last few decades, and will continue to drive the trend of plant invasion in China and probably elsewhere.